„Humor macht kein kranckheit“ - Hick, Christian (DMW - Deutsche Medizinische Wochenschrift, 2018)
Paracelsus was an adventurer in more than one way. We retrace the little that is known about his life and then focus on his adventures in the history of ideas, namely the scientific revolution he brought about for humoral pathology. Following the landmark study of Pagel (1982) we identify two of his conceptions of disease: diseases as fruits and diseases as minerals, discovered by a new science, a “scientia separationis”. Paracelsus did not merely polemize against humoral pathology, but offered a new world view, a new paradigm, so that his endeavor can be characterized with Kuhn (1962) as a scientific revolution.
Keywords: Paracelsus; Humoralpathologie; Krankheitsbegriffe; Wissenschaftliche Revolution